Carvacrol reducesClostridium difficilesporulation and spore outgrowthin vitro. Issue 8 (August 2017) - Mooyottu, Shankumar; Flock, Genevieve; Venkitanarayanan, Kumar
Abstract : Purpose. : Clostridium difficile is an anaerobic spore‐forming pathogen that causes a serious toxin‐mediated enteric disease in humans. Therapeutic agents that are capable of reducing C. difficile spore production could significantly minimize the transmission and relapse of C. difficile infections. This study investigated the efficacy of a food‐grade, plant‐derived compound, carvacrol (CR), in reducing C. difficile spore production, germination and spore outgrowth. Methodology. : Two hyper‐virulent C. difficile isolates (ATCC BAA 1870 and 1805) were grown with or without a sub‐inhibitory concentration (SIC) of CR. Total viable counts and heat‐resistant spore counts were determined at different time intervals. Moreover, spores and vegetative cells were visualized using phase‐contrast microscopy. To determine the effect of CR on C. difficile germination and spore outgrowth, C. difficile spores were seeded in germination medium with or without the SIC and MIC of CR, and spore germination and spore outgrowth were measured by recording optical density at 600 nm. The effect of CR on C. difficile sporulation genes was also investigated using real‐time qPCR. Results. : Carvacrol significantly reduced sporulation in C. difficile and down‐regulated critical genes involved in spore production ( P <0.05). The SIC or MIC of CR did not inhibit C. difficile spore germination; however, the MIC of CR completely inhibited spore outgrowth. Conclusion. : The results suggest that CR could potentially be used to control C. difficile by reducing spore production and outgrowth.